2017
DOI: 10.5812/zjrms.4402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Artemisia dracunculus Aqueous Extract on Blood Sugar, Serum Insulin, Triglyceride and Liver Enzymes in Fructose Drinking Water Male Rats

Abstract: Background: Artemisia are various groups of plants which are used as an herbal medicine in all countries; the present study was designed to evaluate the effects of Artemisia dracunculus (AD) leaves aqueous extract on blood sugar, serum insulin, and triglyceride and liver enzymes in Fructose Drinking water (FDW) male rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
2
2
0
1
Order By: Relevance
“…The serum level of TG in the diabetic rats treated with U. dioica was significantly lower than diabetic rats exposed to L. album extract. Our result is in consistent with that of Shahraki et al (2013) who reported that the treatment with U. dioica caused remarkable decreases in the serum TG concentration when compared to diabetic rats. However in contrast to our present study, Ahangarpour et al (2012) showed significantly increased TG in diabetic rats treated with the U. dioica.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The serum level of TG in the diabetic rats treated with U. dioica was significantly lower than diabetic rats exposed to L. album extract. Our result is in consistent with that of Shahraki et al (2013) who reported that the treatment with U. dioica caused remarkable decreases in the serum TG concentration when compared to diabetic rats. However in contrast to our present study, Ahangarpour et al (2012) showed significantly increased TG in diabetic rats treated with the U. dioica.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were consistent with those of Ahangarpour A et al study (2012), who reported the U. dioica extract remarkably decreased the level of serum LDL and LDL/HDL ratio. Our results were in accordance with those of Shahraki et al (2013) who found that the diabetic rats treated with U. dioica had a remarkable decrease in the level of serum total cholesterol, LDL compared with those of diabetic rats. Dahr et al (2006) also showed that the extract of U. dioica reduced the level of LDL and cholesterol in hypercholestromic diet male rats.…”
Section: Discussionsupporting
confidence: 93%
“…The growth performance of cultured fish species is primarily influenced by food additives capable of stimulating digestive enzymes and synthesizing vitamins, proteins, essential amino acids and unsaturated fatty acids, resulting in increased food utilization and weight gain (Dawood, Koshio, Ishikawa, Yokoyama, et al, 2016; Van Hai, 2015; Radhakrishnan et al, 2014). Shahraki et al (2017) showed that the administration of aqueous extract of tarragon could have a considerable impact on the regulation of carbohydrate metabolism in the body of laboratory rats. They found that the active ingredients in AD extract could increase glucose uptake in cells by increasing the sensitivity to insulin (Ribnicky et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Outros estudos elucidaram bem as atividades antidiabética e hipogliceimiante da planta (GUPTA et al, 2011;LANJHIYANA et al, 2011;SHAHRAKI et al, 2009), encontrando melhora significativa da insulina plasmática em animais portadores de diabetes e redução significativa da glicose de jejum, além de melhora importante nos parâmetros que revelam distúrbios no metabolismo de lipídios, pela diminuição de colesterol, triglicérides, ácidos graxos livres e fosfolipídios em animais submetidos ao tratamento com o extrato em gel de Aloe vera (RAJASEKARAN et al, 2006). O potencial cicatrizante (FALEIRO et al, 2009;MAENTHAISONG et al, 2007;OLIVEIRA et al, 2010) foi evidenciado em muitos estudos, através da maior recuperação na contração das feridas nos experimentos realizados com esse vegetal, comparando-o com o placebo ou com outros tipos de cicatrizantes.…”
Section: Aplicações Clínicas Do Aloe Veraunclassified